Tiempos Nuevos: Socialism, science and technology during the Second Republic - Núñez Rodríguez, Alberto (Hispania Nova, 2021)
The main purpose of this article is to connect the history of science and the history of socialist political culture during the Second Spanish Republic. To that end, the scientific and technical content of Tiempos Nuevos, a journal of municipal studies edited by several socialist councilors of the Madrid City Council led by Andrés Saborit between 1934 and 1936 has been analyzed. Tiempos Nuevos, which was one of the major initiatives of the moderate wing of the Partido Socialista Obrero Español (PSOE) and the Unión General de Trabajadores (UGT), constitutes a key source for the study of the socialist movement during the Republican years, a period characterised by a deep internal crisis. Besides, its content and its collaborators offer a very interesting information about the process of dissemination and popularization of science and technology during the Second Republic.
Keywords: Second Spanish Republic; socialist political culture; socialist press; Tiempos Nuevos; Andrés Saborit